2018
DOI: 10.1038/s41598-018-26411-7
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput screening identified selective inhibitors of exosome biogenesis and secretion: A drug repurposing strategy for advanced cancer

Abstract: Targeting exosome biogenesis and release may have potential clinical implications for cancer therapy. Herein, we have optimized a quantitative high throughput screen (qHTS) assay to identify compounds that modulate exosome biogenesis and/or release by aggressive prostate cancer (PCa) CD63-GFP-expressing C4-2B cells. A total of 4,580 compounds were screened from the LOPAC library (a collection of 1,280 pharmacologically active compounds) and the NPC library (NCGC collection of 3,300 compounds approved for clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
238
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(238 citation statements)
references
References 50 publications
0
238
0
Order By: Relevance
“…GW4869 and manumycin-A were the first and few molecules known to inhibit exosome secretion [6,20]. Recently, prostate cancer cells were screened with small molecules to test their effects on exosome production [5,6], but the molecules identified in that screen (tipifarnib, nitrefazole, pentetrazol, etc.) have not been tested or shown to work in other cell types [5], despite evidence of cell type-specific effects of small molecules on exosome secretion [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GW4869 and manumycin-A were the first and few molecules known to inhibit exosome secretion [6,20]. Recently, prostate cancer cells were screened with small molecules to test their effects on exosome production [5,6], but the molecules identified in that screen (tipifarnib, nitrefazole, pentetrazol, etc.) have not been tested or shown to work in other cell types [5], despite evidence of cell type-specific effects of small molecules on exosome secretion [6].…”
Section: Discussionmentioning
confidence: 99%
“…A recent screening approach in prostate cancer cells identified 23 significant exosome stimulators and inhibitors [5], with fenoterol, norepinephrine, forskolin, methyldopamine, and mephenesin the top five stimulators. However, the screen was limited to a single prostate cancer cell type, and the identified molecules have yet to be tested or shown to work in other cell types [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence indicates that changes in cancer cells and the tumor microenvironment can regulate the biogenesis, composition, and function of TDEs, however relative little is known about many of these processes, which could offer new avenues for tumor interventions. Indeed, at least one recent study has utilized a high‐throughput screening approach to identify the potential of repurposed drugs to act as selective inhibitors of exosome biogenesis . This approach represents a tempting means to limit the negative local and systemic effects of TDEs on tumor development and metastasis, including their effects on the antitumor immune response.…”
Section: Concluding Remarks and Future Perspectivementioning
confidence: 99%
“…Indeed, at least one recent study has utilized a high-throughput screening approach to identify the potential of repurposed drugs to act as selective inhibitors of exosome biogenesis. 188 This approach represents a tempting means to limit the negative local and systemic effects of TDEs on tumor development and metastasis, including their effects on the antitumor immune response. However, since all cells appear to secrete exosomes, this type of intervention appears likely to cause significant side-effects unless drugs can be identified that target tumorselective mechanisms regulating exosome biogenesis.…”
Section: Concluding Remarks and Future Perspectivementioning
confidence: 99%